2019
DOI: 10.1177/1049732319843499
|View full text |Cite
|
Sign up to set email alerts
|

Psychologists’ Perspectives on the implementation of Psychological Therapy for Psychosis in the Acute Psychiatric Inpatient Setting

Abstract: Psychological therapies should be delivered in psychiatric inpatient settings to people experiencing psychosis. However, inpatient populations present with complex needs and usually are admitted only briefly. This makes the delivery of psychological therapies for people experiencing psychosis particularly challenging. Our aim was to explore the adaptations required to deliver psychological therapies to this population from the perspective of inpatient psychological practitioners. Twelve participants were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 14 publications
4
37
0
Order By: Relevance
“…This means, for the purpose of developing a psychological service model for a randomized controlled trial, it is not known whether it is possible to deliver all three levels across different acute mental health wards. However, we would argue that this highlights the importance of psychologist ability to flexibly apply the model, in line with prior research, which demonstrates the importance of flexible approaches to working on acute mental health wards to facilitate staff and patient adoption of psychological services (Wood et al, 2019). Another limitation is that the psychologists only recorded their activities across one random week per month as we did not want to overburden the psychologists due to the time it took to complete the checklist.…”
Section: Discussionsupporting
confidence: 81%
“…This means, for the purpose of developing a psychological service model for a randomized controlled trial, it is not known whether it is possible to deliver all three levels across different acute mental health wards. However, we would argue that this highlights the importance of psychologist ability to flexibly apply the model, in line with prior research, which demonstrates the importance of flexible approaches to working on acute mental health wards to facilitate staff and patient adoption of psychological services (Wood et al, 2019). Another limitation is that the psychologists only recorded their activities across one random week per month as we did not want to overburden the psychologists due to the time it took to complete the checklist.…”
Section: Discussionsupporting
confidence: 81%
“…The 16 articles included six qualitative papers (Awenat et al, 2018(Awenat et al, , 2019Donaghay-Spire et al, 2016;Small et al, 2018;Tyrberg et al, 2017;Wood et al, 2019), one RCT (Wood et al, 2018), four non-randomised trials (Chang et al, 2014;Fife et al, 2019;Gaudiano et al, 2020;Paterson et al, 2019), one mixed methods design (Heriot-Maitland et al, 2014) and four case series (Davidson et al, 2009;Folke et al, 2015;Jacobsen & Clark, 2016;Moore et al, 2019).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The qualitative studies were of good methodological quality. The data collection methods were adequate as semi-structured interviews were audio-recorded and transcribed verbatim (Awenat et al, 2018(Awenat et al, , 2019Donaghay-Spire et al, 2016;Small et al, 2018;Tyrberg et al, 2017;Wood et al, 2019). The single RCT was of low methodological quality because the assessors were not blinded to intervention status and there were incomplete outcome measures (Wood et al, 2018).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…There have been calls for a wider range of positive ward activities and, particularly, psychological therapies to be made available to inpatients (British Psychological Society, 2015). Qualitative research on the perspectives from members of multidisciplinary teams, including mental health nurses, also indicates that psychological therapies are valued in key areas (Wood, Williams, Billings and Johnson, 2019). They were reported to be helpful in fostering patients' understanding of their difficulties and so ameliorating interpersonal difficulties with staff.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, therapists have reported they are unable to deliver a structured approach to therapy, often adapting by providing "stand alone" sessions, causing concerns over whether practice is evidence based (Small, Pistrang, Huddy and Williams, 2018). Similarly, Wood Williams, Billings and Johnson (2019) reported that therapists prioritise "immediate crises" to address risk and facilitate discharge, rather than thinking about the wider context of individuals' lives, ongoing factors precipitating an admission or, repeated stays in hospital. This focus on discharge planning often contradicts patients' preferences for space and time to think broadly about their experiences and adjust to ward life (Small et al 2018).…”
Section: Introductionmentioning
confidence: 99%